Head CT Guidelines Following Concussion Among the Youngest Trauma Patients: Can We Limit Radiation Exposure Following Traumatic Brain Injury? - Harvell, Bryan J.; Helmer, Stephen D.; Ward, Jeanette G.; Ablah, Elizabeth; Grundmeyer, Raymond; Haan, James M. (Kansas Journal of Medicine, 2019)
Introduction. Recent studies have provided guidelines on the use of head computed tomography (CT) scans in pediatric trauma patients. The purpose of this study was to identify the prevalence of these guidelines among concussed pediatric patients. Methods. A retrospective review was conducted of patients four years or younger with a concussion from blunt trauma. Demographics, head injury characteristics, clinical indicators for head CT scan (severe mechanism, physical exam findings of basilar skull fracture, non-frontal scalp hematoma, Glasgow Coma Scale score, loss of consciousness, neurologic deficit, altered mental status, vomiting, headache, amnesia, irritability, behavioral changes, seizures, lethargy), CT results, and hospital course were collected. Results. One-hundred thirty-three patients (78.2%) received a head CT scan, 7 (5.3%) of which demonstrated fractures and/or bleeds. All patients with skull fractures and/or bleeds had at least one clinical indicator present on arrival. Clinical indicators that were observed more commonly in patients with positive CT findings than in those with negative CT findings included severe mechanism (100% vs. 54.8%, respectively, p = 0.020) and signs of a basilar skull fracture (28.6% vs. 0.8%, respectively, p = 0.007). Severe mechanism alone was found to be sensitive, but not specific, whereas signs of a basilar skull fracture, headache, behavioral changes, and vomiting were specific, but not sensitive. No neurosurgical procedures were necessary, and there were no deaths. Conclusions. Clinical indicators were present in patients with positive and negative CT findings. However, severe mechanism of injury and signs of basilar skull fracture were more common for patients with positive CT findings. Kans J Med 2018;11(2):38-43.